Utility of Tumor Capsule Thickness as a Predictor of Invasion in Encapsulated Follicular Variant of Papillary Thyroid Carcinoma and a Diagnostic Tool for Noninvasive Follicular Thyroid Neoplasm With Papillary-Like Nuclear Features. (February 2020) - French, Brenda; Hattier, Georgette; Mardekian, Stacey K.
Context . Noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) is an extremely indolent subset of noninvasive encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC). These lesions share certain features including a delimiting fibrous capsule, and they are distinguished by detailed histological criteria. Objective . We sought to identify whether tumor capsule thickness differs significantly between NIFTP and noninvasive EFVPTC lesions. We also compared tumor capsule thickness between noninvasive and invasive EFVPTC in order to evaluate its utility as a predictive marker of invasion. Design . Encapsulated follicular thyroid neoplasms with papillary-like nuclear features diagnosed over a 3-year period at a single institution were subcategorized into NIFTP, noninvasive EFVPTC, and invasive EFVPTC based on current diagnostic criteria. Maximum tumor capsule thickness for each lesion was measured. Results . A total of 92 lesions (39 NIFTP, 15 noninvasive EFVPTC, and 38 invasive EFVPTC) were evaluated. Tumor capsule thickness was significantly thinner in NIFTP ( P = .022) and significantly thicker in invasive EFVPTC ( P = .0006) when compared with noninvasive EFVPTC. Conclusions . Tumor capsule thickness may be an additional useful marker when distinguishing between NIFTP and noninvasive EFVPTC. A capsule thickness of greater than 0.2 mm should raise suspicion for EFVPTC and thus prompt more thorough review of the submitted tissue for NIFTP exclusionary criteria. Additionally, if capsular and/or vascular invasion are not present on initial slides of an entirely evaluated capsule of EFVPTC that exceeds 0.5 mm in thickness, the pathologist should order additional tissue levels to ensure that a small focus of invasion is not missed.